Utilising MIMO for Location and Positioning in IMT -Advanced Systems - Awang Md Isa, Azmi (2010)
With the advances of multiple input multiple output (MIMO) technology as one of IMT-Advanced features, it has hecome feasible to adopt the technology into the mobile location scenario. By exploiting the multipath characteristics of the MIMO system, it is possible to estimate the position of mobile stations (MS) by considering the capability of MIMO to mitigate the non line of sight (NLOS) conditions that deteriorate the accuracy of location estimation. In this paper we developed geometric approach by utilizing the advantages of MIMO system and employ the time of arrival (TOA) as range measurements for improving location estimation. The performance of the proposed method has been evaluated through computer simulation. The results of our simulation demonstrate that the proposed algorithm is significantly more effective in location accuracy than the conventional technique (LLS algorithm) and MIMO antenna configurations can achieve high accuracy for location estimation which meets the Federal Communications Commission (FCC) requirements.